European Lobbying : An Occupational Field between Professionalism and Activism (Edition 1) - Lahusen, Christian (Taylor and Francis, 2023)
Lobbying is an integral part of the political reality of the European Union and a highly competitive and dynamic field of interest groups. This book takes a systematic look at lobbyists in order to broaden our understanding of the staff entrusted with the responsibility of influencing European politics. Who are the European lobbyists? What are their professional backgrounds, career patterns, practices, and beliefs? The study uses a sociological framework to explore the professionalisation and professionalism of the field across national proveniences, policy fields and interest groups, and develops a systematic analysis that considers three different dimensions: occupational patterns, shared knowledge and common convictions. Based on original research that combines in- depth interviews with survey data, European Lobbying demonstrates that European lobbying is a firmly established and highly professionalised métier. In an organisational field characterised by growth, pluralisation and increasing competition, the professional staff contributes to the homogenisation of European lobbying and the marginalisation of other, non- professionalised forms of interest representation. It will therefore appeal to scholars and students of sociology and politics with interest in European studies, European Union politics and the sociology of the professions. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license